Measurement of physical activity and sedentary behavior: a research group-based analysis - Romanzini, Marcelo (2022)
The present study characterized the Brazilian research groups that have research lines focused on the measuring of physical activity and/or sedentary behavior. Authors of original articles that involved the development, adaptation, translation, and quality testing of measures of physical activity/sedentary behavior instruments in the Brazilian population were invited to answer an online instrument containing 19 questions to identify leaders and general characteristics of research groups. Twenty-eight research groups were identified, the pioneer being created in the 1970’s and the majority in the last two decades. While the Southeast region had the highest concentration of groups, the absence of groups was identified in the North and Midwest regions. The measurement methods most tested by these groups were subjective, predominantly questionnaires (n = 24), followed by objective methods using accelerometers (n = 18) and pedometers (n = 9). Several connections (permanent partnerships with other groups/institutions) were identified at national and international levels, especially with countries in North America, Europe, and Australia. It is expected that the results of the present study can stimulate collaborative actions between Brazilian groups and researchers to reduce regional inequalities and improve the production of knowledge in the area of measuring physical activity and sedentary behavior.